Identification of host defenses in the Drosophila gut using genome-scale RNAi - Ferrandon, Dominique (Henry Stewart Talks, 2014)
Why use drosophila to study immunity?, Drosophila digestive tract, Intestinal barriers against pathogens, The imd pathway in preventing infection, Serratia marcescens, an opportunistic pathogen, Genome wide RNA-I screening to identify essential genes for host defense, Gene ontology of the hits from RNA-I screening, The JAK/STAT pathway, The components of host defenses to infections, Serratia hemolysins